Different initiatives across Europe to enhance losartan utilization post generics: impact and implications - Moon, James C.; Godman, Brian; Petzold, Max; Alvarez-Madrazo, Samantha; Bennett, Kathleen; Bishop, Iain; Bucsics, Anna; Hesse, Ulrik; Martin, Andrew; Simoens, Steven; Zara, Corinne; Malmström, Rickard E. (Frontiers in Pharmacology, 2014)
Introduction: There is an urgent need for health authorities across Europe to fully realise potential savings from increased use of generics to sustain their healthcare systems. A variety of strategies were used across Europe following the availability of generic losartan, the first angiotensin receptor blocker [ARB] to be approved and marketed, to enhance its prescribing versus single-sourced drugs in the class. Demand-side strategies ranged from 100% co-payment for patented ARBs in Denmark to no specific measures. We hypothesised this heterogeneity of approaches would provide opportunities to explore prescribing in a class following patent expiry. Objective: Contrast the impact of the different approaches among European countries and regions to the availability of generic losartan to provide future guidance. Methodology: Retrospective segmented regression analyses applying linear random coefficient models with country specific intercepts and slopes were used to assess the impact of the various initiatives across Europe following the availability of generic losartan. Utilisation measured in defined daily doses (DDDs). Price reductions for generic losartan were also measured. Results: Utilisation of losartan was over 90% of all ARBs in Denmark by the study end. Multiple measures in Sweden and one English primary care group also appreciably enhanced losartan utilisation. Losartan utilisation actually fell in some countries with no specific demand-side measures. Considerable differences were seen in the prices of generic losartan. Conclusion: Delisting single-sourced ARBs produced the greatest increase in losartan utilisation. Overall, multiple demand-side measures are needed to change physician prescribing habits to fully realise savings from generics. There is no apparent ‘spill over’ effect from one class to another to influence future prescribing patterns even if these are closely related.